PENINGKATAN DAYA SAING UMKM PARIWISATA MELALUI PELATIHAN SERVICE EXCELLENT DAN STRATEGI SOCIAL MEDIA MARKETING DI JAWA TIMUR - Fatchur Rohman; Raditha Hapsari; Rr Ayu Firdausiah; Ani Kartikasari; Eka Putri Rifandani; Eka Fais Wahyuli (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
The tourism sector plays a strategic role in Indonesia’s economy, including in East Java Province, which holds significant potential but whose contribution to the Regional Gross Domestic Product (RGDP) remains limited. This activity aims to enhance the competitiveness and sustainability of MSMEs in the tourism sector through service excellence training and social media marketing mentoring. The method involves several stages: problem identification through Focus Group Discussions (FGDs), training sessions, mentoring, and evaluation of MSME progress. The FGDs revealed two primary challenges: low service quality and limited utilisation of social media for marketing. The service excellence training focused on improving customer service capabilities, while the social media marketing mentoring emphasised practical skills in creating digital content and using analytical tools. The results demonstrated increased knowledge and understanding among participants regarding the importance of service quality and digital marketing strategies. However, regular activity on social media remains limited due to time constraints and resource limitations. Enhancing the understanding of service excellence and boosting marketing efforts via social media are essential for helping tourism-related MSMEs in East Java to survive and grow. In conclusion, the training and mentoring initiatives proved effective in strengthening the capacity of tourism MSMEs. It is recommended that follow-up actions include advanced training and ongoing technical support to ensure the sustainability of digital transformation and service quality improvement, which in turn will contribute to competitive tourism and local economic growth.